Sharing Local Public Health Services Across Jurisdictions: Comparing Practice in 2012 and 2014 - Madamala, Kusuma (Front Public Health Serv Syst Res, 2016)
OBJECTIVE: Describe cross-jurisdiction service sharing (CJS) by local and tribal health departments (LHD) in Wisconsin in 2014 compared to 2012. DESIGN: An online survey of 91 LHD directors in Wisconsin was conducted. Results were compared to the results of a 2012 survey. Characteristics of CJS arrangements and differences in results by population size, geographic region, and governance type were described. Standardized proportion differences (h) were estimated using the arcsin transformation. Confidence intervals were estimated using unconditional exact confidence intervals for the difference of proportions.(8) A forest plot of the estimates and confidence intervals was generated to visualize change in CJS for each population category. RESULTS: Seventy-eight percent of respondents in 2014 reported currently sharing services compared to 71% of respondents in 2012. Positive effect sizes indicate increased sharing in year 2014 relative to 2012. CJS was more frequent for LHD serving smaller jurisdictions, consistent with both 2012 survey results and national findings. All governance types continue to engage in sharing public health services. IMPLICATIONS: Cross jurisdictional service sharing is widespread and increasing in Wisconsin, implying that it is a useful strategy for providing public health services under some circumstances. Educating public health practitioners and students about CJS strategies in public health is recommended.